Kota Cerdas Untuk Siapa? Studi Kasus Kanal Partisipasi Warga Medan, Jakarta, dan Surabaya - Hasanuddin, Dian Zuchraeni Ekasari (Universitas Diponegoro, Indonesia, 2021)
Smart City is inevitable in a world of rapid technological developments and accompanied by various urban challenges. The implementation of smart city could become very technical and mechanistic, in a way that deprived from its essential role as a means of citizens’ livelihood. This concern is reflected in the main critics (Hollands, 2008; Krivy, 2016; Cardullo & Kitchin, 2018;) of the technocratic, unequal, and less citizen-centric characters of smart city. Since most of the criticism resulted from research on smart cities in other countries, it is interesting to examine smart citizen aspect in Indonesia especially as smart city has been implemented in more than a hundred cities within a decade. Therefore, this paper explores the existence of citizen digital participation channels in Medan, Jakarta and Surabaya, as well as its position in the classic Ladder of Citizen Participation from Arnstein (1969) and the recent Ladder of Participation in Civic Technology from Offenhuber (2015). The analysis finds the highest ladder of participation is Partnership in the form of Hackathon in Jakarta. Placation is the second highest ladder found in Medan, Surabaya, and Jakarta through Development Planning Deliberations forum or Musrenbang. These findings along with its relation to smart governance and smart people aspects provide a portrait of citizens' significance in the multidimensional development of Indonesian Smart City.